Antioxidant Activity of Spices and Their Impact on Human Health: A Review - Alexander Yashin; Yakov Yashin; Xiaoyan Xia; Boris Nemzer (MDPI AG, 2017)
Antioxidants are substances that prevent oxidation of other compounds or neutralize free radicals. Spices and herbs are rich sources of antioxidants. They have been used in food and beverages to enhance flavor, aroma and color. Due to their excellent antioxidant activity, spices and herbs have also been used to treat some diseases. In this review article, the chemical composition and antioxidant activity of spices and culinary herbs are presented. The content of flavonoids and total polyphenols in different spices and herbs are summarized. The applications of spices and their impacts on human health are briefly described. The extraction and analytical methods for determination of antioxidant capacity are concisely reviewed.